The Impact of Very Large Online Platforms on Fundamental Rights - Joó, Patrik Zsolt (Közigazgatási és Infokommunikációs Jogi PhD Tanulmányok, 2025)
Since the early 2010s, online platforms have generated most internet traffic, embedding themselves in daily life while shaping political, cultural, and economic processes. Yet profit-driven platforms, powered by opaque algorithms and advertiser-oriented business models, pose serious challenges to the protection of fundamental rights—especially freedom of expression, access to information, and privacy. This paper analyses the impact of Very Large Online Platforms (VLOPs) on fundamental rights and examines the European Union’s regulatory responses, with particular emphasis on the Digital Services Act (DSA) and proceedings under Article 66 before the European Commission. The study draws on EU legislation, public documentation of ongoing cases, and selected international and Hungarian scholarship. Focusing on the relationship between VLOPs and freedom of expression under Article 11 of the Charter of Fundamental Rights of the European Union, the paper argues that the DSA establishes an ex ante framework for rights protection. However, in the absence of developed case law, the effectiveness of this regime remains uncertain.